Demography and migration : population trajectories from the Neolithic to the Iron Age : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Lachenal, Thibault,; Roure, Réjane,; Lemercier, Olivier, (Archaeopress Archaeology, 2020)
This volume presents combined proceedings of two complementary sessions of the XVIII UISPP World Congress (Paris, 2018). These sessions aimed to identify demographic variations during the Neolithic and Bronze Age and to question their causes while avoiding the potential taphonomic and chronological biases affecting the documentation.